Advantage and Choice: Social Relationships and Staff Assistance in Assisted Living - Burge, Stephanie (Oxford University Press, 2010)
OBJECTIVES. To understand how “cumulative inequality” (CI), expressed as individual advantage and choice, and “external social supports” contribute to the quality of social relationships and perceptions of staff assistance for older individuals in different assisted living (AL) settings. METHODS. Data are from 429 cognitively intact AL residents aged 60 years and older interviewed for the Florida Study of Assisted Living. Bivariate and multivariate statistical analyses show how individual advantage and choice and external social networks influence respondents’ social relationships and staff assistance in AL. RESULTS. Controlling for resident and facility characteristics, being able to pay privately enhances resident satisfaction with staff assistance and having control over the move to AL is positively associated with perceptions of staff relationships and assistance. Maintaining contact with pre-AL friends predicts quality of coresident relationships, as does family contact. Regular contact with family buffers some of the disadvantages associated with CI for perceptions of staff relationships but not perceptions of staff assistance. DISCUSSION. Individual advantage and choice influence the quality of staff relationships and assistance for AL residents but matter little for coresident relationships. External social relationships buffer some of the risks associated with CI for perceptions of staff relationships but not perceived quality of staff assistance. Findings highlight outcomes associated with CI, including predictable risks that disadvantaged elders face in particular types of AL settings, differential advantages others enjoy that influence positive perceptions of staff relationships and staff assistance, and the enduring importance of supportive social relationships.